Additive‐Free Tunable Transport and Assembly of Floating Objects at Water‐Air Interface Using Bubble‐Mediated Capillary Forces. Issue 7 (30th January 2017) - Vinay, Thamarasseril Vijayan; Banuprasad, Theneyur Narayanaswamy; George, Sajan Daniel; Varghese, Soney; Varanakkottu, Subramanyan Namboodiri
Abstract : An additive‐free and reconfigurable assembly strategy based on capillary interaction between an air‐bubble and floating object is demonstrated. The method is capable of long‐range transport, assembly, and on‐demand disassembly of floating objects at the water–air interface, by simply controlling the dynamics of the air bubble.